ESG Disclosure, Financial Performance, and Firm Value: The Mediating Role of Competitive Advantage - Haya Inayah Khaulah; Anwar Azazi; Ana Fitriana; Mochammad Ridwan Ristyawan; Uray Ndaru Mustika (Al-Qalam Institue, 2026)
Understanding how sustainability disclosure and financial performance shape firm value remains an important issue in corporate governance and capital market studies. The purpose of this research is to examine the influence of Environmental, Social, and Governance (ESG) disclosure and financial performance on firm value, with competitive advantage acting as a mediating variable. A quantitative approach was employed using panel data from 46 publicly listed companies over the 2021–2024 period. The analysis utilized panel regression combined with path analysis to evaluate both direct and indirect relationships among variables. The findings indicate that financial performance has a positive and significant effect on firm value, confirming its central role in determining market valuation. In contrast, ESG disclosure does not show a significant direct effect on firm value. Furthermore, ESG disclosure demonstrates a negative relationship with competitive advantage, while financial performance positively influences competitive advantage. Mediation analysis reveals that competitive advantage does not mediate the relationship between ESG disclosure and firm value but partially mediates the relationship between financial performance and firm value. These findings imply that companies should strengthen financial performance as a strategic foundation while integrating ESG practices more effectively to enhance long-term competitive positioning and firm value.